Crystal structure of baricitinib, C16H17N7O2S. Issue 3 (September 2022) - Lee, Yewon; Wang, Yulong; Khalifah, Peter G.; Stephens, Peter W.; Kaduk, James A.; Gates-Rector, Stacy; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of baricitinib has been solved and refined using synchrotron X-ray powder diffraction data and optimized using density functional techniques. Baricitinib crystallizes in space group I 2/ a (#15) with a = 11.81128(11), b = 7.06724(6), c = 42.5293(3) Å, β = 91.9280(4)°, V = 3548.05(5) Å 3, and Z = 8. The crystal structure is characterized by hydrogen-bonded double layers parallel to the ab -planes. The dimers form a graph set R2, 2(8). The sulfone ends of the molecules reside in the interlayer regions. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™ (PDF ® ).